Упростите выражения: 1)а+(-b)-(-2a); 2)-а-(+а)+2b-(-b); 3)-a-(-b)-4a; 4)-a-(+3a)+(-b)-b. Заполните рамочки в верном равенстве: 1 ) -7-(?)=-2; 2 ) ? -(-6)=4; 3 ) ? -(+10)=-7; 4 ) 2 -(?)=0; 5 ) - 6 -(?)=-3.
Упростите выражения:
1)а+(-b)-(-2a);
2)-а-(+а)+2b-(-b);
3)-a-(-b)-4a;
4)-a-(+3a)+(-b)-b.
Заполните рамочки в верном равенстве:
1 ) -7-(?)=-2;
2 ) ? -(-6)=4;
3 ) ? -(+10)=-7;
4 ) 2 -(?)=0;
5 ) - 6 -(?)=-3.
Ответ(ы) на вопрос:
1)3a-b
2)-2a+3b
3)-5a+b
4)-4a-2b
1)-5
2)-2
3)3
4)2
5)-3
a+(-b)-(-2a)=a+2a-b=3a-b
-a-(+a)+2b-(-b)=-a-a+2b+b=-2a+3b
-a-(-b)-4a=-a+b-4a=-5a+b
Не нашли ответ?
Похожие вопросы